PENGARUHPENERAPAN TEKNOLOGI ROBOTIC PROCESS AUTOMATION TERHADAP EFEKTIFITAS PROSES AKUNTANSI DI PERUSAHAAN - Benyamin Jeman; Vivi Adeyani Tandean (Institut Teknologi dan Bisnis Kristen Bukit Pengharapan, 2024)
This investigation aims to study the consequences of human-machine collaboration in accounting and develop methods to address potential negative impacts such as human-robot competition, unintentional changes in organizational structure, decline in skills and skills development, knowledge management, and bias of knowledge.The study uses a library review method used as a basis to suggest future research direction related to the challenges and issues associated with RPAs in accounting. The results of this study show that, RPA has the potential to transform the field of accounting and highlight several areas of future research, including the consequences of human-machine collaboration, limitations and obstacles to automation, as well as the development of new roles and skills in accountancy education. In addition, understanding the impact and potential of RPAs in accounting fully is required before proceeding with research into the same area.